Preceding Administration of Minocycline Suppresses Plastic Changes in Cortical Excitatory Propagation in the Model Rat With Partial Infraorbital Nerve Ligation - Zama, Manabu; Fujita, Satoshi; Nakaya, Yuka; Tonogi, Morio; Kobayashi, Masayuki (Frontiers in Neurology, 2019)
Neuropathic pain is known to be attributable to the injured nerve, a postoperative problem induced by surgery. The infraorbital nerve (ION), a branch of the trigeminal nerve, innervates to the facial and oral regions and conveys somatosensory information to the central nervous system. The partial ligation of ION (pl-ION) is a method to mimic chronic trigeminal neuropathic pain and behavioral abnormality. To counteract induction of such abnormal pain, the effective pharmacological treatment is desired. Although recent studies have revealed the molecular mechanisms regarding chronic pain, estimation of the effectiveness of the pharmacological treatment has not been well-provided especially in the central nervous system so far. Here we examined whether pl-ION induces plastic changes in the cerebral cortex and investigated effects of minocycline on the cortical plastic changes. We performed the pl-ION to Wistar male rats (4–5 weeks old), and confirmed a mechanical nocifensive behavior in response to the mechanical stimulation with von-Frey filaments. The withdrawal threshold to mechanical stimuli of the whisker pad was decreased 1 day (1 d) after pl-ION, which continued up to 14 d after pl-ION, suggesting that pl-ION model rats presented allodynia and enhanced the response sustained at least for 14 d after pl-ION. Next, cerebrocortical activities were evaluated 3 d after pl-ION (3d-pl-ION) by the optical imaging with a voltages-sensitive dye, RH1691, to quantify the response to electrical stimulation of the whisker pad skin, mandibular molar dental pulp, and mentum skin. Electrical stimulation to the whisker pad skin induced smaller excitation in the primary sensory cortex (S1) of 3d-pl-ION in comparison to that in the sham. In contrast, cerebral cortical responses to the mandibular molar dental pulp and mentum skin stimuli increased both in S1, and the secondary somatosensory and insular oral region (S2/IOR) after pl-ION. Administration of minocycline (30 mg/kg/d) from 1 d before to 2 d after pl-ION partially recovered the pl-ION-induced changes in cortical excitation in S1 and S2/IOR in 3d-pl-ION. These results suggest that somatosensory and insular cortical excitation is changed by pl-ION, and the preceding injection of minocycline counteracts the plastic changes in the cortical activities.